Effect of Film Thickness on Narrowband Thermochromic Liquid Crystal Calibration - Abdullah, Nadia (2009)
Thermochromic liquid crystals (TLCs or TLC) are complex organic substances which selectively reflect visible light as function of temperature. Narrowband TLCs are attractive for temperature measurements due to their higher precision in temperature measurements associated with their narrow bandwidths, and calibrations of narrowband TLCs are less affected by variations in illumination-viewing angles and background illumination. In order to properly utilize narrowband TLCs and intensitymatching methods for quantitative temperature measurements, it is important to investigate film thickness effects on intensity-based calibrations of narrowband TLCs, which have been previously ignored in previous research. Film thicknesses of 10, 20, 30, 40 and 50 μm were investigated on green intensity-based calibrations of R35C1W narrowband TLC during heating and cooling. The results showed an increase in magnitude of peak green intensity with increasing film thickness, with a percentage increase of approximately 18% when film thickness increased from 10 μm to 50 μm. The results also showed an inconsistent shift in peak green temperature, with a maximum temperature shift of 0.40ºC, suggesting that film thickness effects may be insignificant for narrowband TLCs compared with wideband TLCs. A theoretical method for estimating the volume of coating formulation required to achieve a desired film thickness was presented in this research, based on the film coverage and dry solids content of the TLCs. Results were presented for seven samples of sprayable narrowband TLCs with desired film thicknesses of 10, 20, 30, 40 and 50 μm based on a square shaped model surface area. The percentage uncertainties in volume of coating formulation was obtained to be significant, within 57 – 67%, however, the results were attributed mainly to the lack in accuracy of the electronic balance, which was ± 1 g. Simulation results showed that if the accuracy was increased to ± 0.001 g, the percentage uncertainties decreased to less than 5% for all samples. The method is easily implemented, and is likely to be beneficial to users intending to employ sprayable TLCs for temperature measurements. In this research, a graphical user interface (GUI) was developed to process images and data in transient calibration of TLCs. The GUI functions to generate full intensity-based calibration curves based on single colour intensity in the Red-Green- Blue (RGB) colour space. The GUI greatly simplifies, streamlines and automates image and data processing, which at present, is carried out by low-level programming and keyboard-entered commands. The GUI is likely to be a useful tool for users intending to utilize TLCs for temperature measurements.